Insights into Factors Influencing Thermoplastic Elastomer (TPE) Foam Production and the Role of Induced Crystallization - Nigus Maregu Demewoz (Advances in Polymer Technology)
This review provides a comprehensive overview of the multifaceted factors influencing TPE foam production, with a specific focus on the intriguing role of induced crystallization. TPE foams excel in versatility and cost-effectiveness, yet their production faces several challenges, that significantly impact their final characteristics. The examination encompasses a range of factors, including solubility, diffusivity, interfacial tension, rheology, foaming parameters, nucleating agents, and the intricate influence of induced crystallization on TPE foam structure and performance. In TPE, crystallinity can be induced through various means including gas sorption, stress concentration, extrusion, annealing, and self-nucleation. These induced crystals serve as nucleation sites for heterogeneous nucleation during foaming. The advancements achieved in polymer foam are thoroughly evaluated in terms of both progress and limitations, drawing insights from various research findings. Furthermore, the review examines recent developments and explores the effects of induced crystallization on TPE foam.